Pengaruh Brand Image, Store Atmosphere, Online Customer Review Terhadap Keputusan Pembelian (Studi Pada Rena Factory Outlet Kab. Tuban) - Irawan, Alfina Zahra; Djaelani, Abdul Kodir; Millaningtyas, Restu (UNIVERSITAS ISLAM MALANG, 2024)
Abstract Rena Factory Outlet is one of the shopping centers in Tuban Regency which has complete facilities in a modern style. This is what makes researchers want to observe these problems, As a result, the purpose of this study was to determine how the brand image, store atmosphere, online customer reviews on customer purchasing decisions for Rena Factory Outlet Kab. Tuban. This study uses quantitative methods using non-probability sampling techniques because the population is unknown and in determining the sample for research, purposive sampling techniques are used using the Malhotra formula by taking a sample of 80 consumers who have visited and bought at Rena Factory Outlet by distributing questionnaires using google form through social media. The analysis method uses the SPSS version 25.0 application. The results of the Rena Factory Outlet study show that brand image, store atmosphere, online customer reviews tested simultaneously have significant results and influence purchasing decisions. Partially, the variables of brand image and store atmosphere have has a positive and significant effect on consumer purchasing decisions, however, the online customer review factor has a positive but insignificant effect on purchasing decisions. Keywords: Brand Image, Store Atmosphere, Online Customer Review.